The Relationship Between Microbial Communities in Coffee Fermentation and Sense and Metabolite Profiles of Finished Products - Tatsaporn Todhanakasem; Ngo Tai; Soisuda Pornpukdeewattana; Theppanya Charoenrat; Briana Young; Songsak Wattanachaisaereekul (My University, 2024)
Abstract Coffee is a critical agricultural commodity and is used to produce premium beverages enjoyed by people worldwide. The microbiome of coffee beans has proven to be an essential tool that improves the flavor profile of coffee by creating aromatic flavor compounds through natural fermentation. Study of the microbial diversity of coffee beans has contributed to methods for rapid fermentation, as well as creating better quality of the final product. This study investigated the natural microbial consortium during wet process fermentation of coffee onsite in Thailand. Our study found 64 genera of bacteria and 59 genera of yeast/ fungi present during the fermentation process. A correlation between microbial diversity and biochemical characteristics including flavor, aroma and metabolic attributes was investigated.
Keywords: Coffee research and impacts